Claim Movements in Capitalism: Some Comments for its Discussion - Piedra, Jonathan (2023)
In today’s capitalist societies, movements such as Black Lives Matter, #MeToo emerge as forces that seek to challenge power structures, promoting social change. These movements impact politics, economics, and culture, raising questions about the possibilities and limitations of collective action in an environment dominated by the logic of the market. Although they fight for the rights and welfare of marginalized groups, some argue that they do not demand a systemic change in the prevailing economic model and that in certain circumstances they may adapt to capitalist logic rather than opposing it. This article analyzes how these movements either challenge or reinforce capitalist power structures through a philosophical analysis of their dynamics, challenges, and opportunities within the framework of capitalism. It is argued that while these movements have raised awareness of specific issues, such as racial discrimination and sexual harassment and abuse, they can be limited in their ability to generate systemic change and challenge the capitalist logic that perpetuates inequalities. Capitalism tends to reproduce and reinforce dominant rules and power structures, which can lead to more limited and superficial approaches to the fight for equality and justice.